Enhanced DME Carrier Phase: Concepts, Implementation, and Flight‐test Results. Issue 3 (28th August 2013) - Li, Kuangmin; Pelgrum, Wouter
ABSTRACT: This paper presents the principle, execution, and analysis of a flight‐test methodology to assess the performance potential of future enhanced Distance Measuring Equipment (eDME) concepts, by using current legacy DME transponder equipment and Radio Frequency (RF) data recordings of both the transmitted and received DME signals. First, the collected DME flight test data is analyzed for received DME signal level, noise performance, and legacy half‐amplitude ranging performance. Second, the concept of DME carrier‐phase is introduced. The measured DME carrier phase tracking performance is compared with theoretical limits. Finally, several applications of DME carrier phase are discussed, implemented, and analyzed. Carrier‐smoothed pulse range significantly reduces the noise and multipath of the measured ranges, pulse minus carrier characterizes the multipath on the pulse‐ranging, and ultra‐precise velocity, obtained from successive changes in DME carrier phase, significantly improves the performance of, for example, collision avoidance algorithms and integrated DME‐inertial systems. Copyright © 2013 Institute of Navigation.